STRICT LIABILITY FOR BREACH OF THE LAWS OF THE WAR BETWEEN ISRAEL AND PALESTINS IN GAZA - Dio Prasetyo Budi; Ilhamda Fattah Kaloko (Airlangga Development Journal, 2023)
Feuds and conflicts that occur in the world are dynamics that occur and things that cannot be avoided by the state. Conflicts between Israel and Palestine occur repeatedly, but the realization of international accountability has not been in accordance with existing rules. The existence of events that resulted in casualties in the war must be accounted for by Israel as a State, as well as the individuals involved. As a result of this action, the perpetrators of war crimes must be held accountable under international law. The problem with this article is what is the responsibility of the State of Israel for violating the laws of war? The conclusion of this article is: There is no responsibility of the State of Israel for violations of the laws of war, from every violation of international law Israel remains free from punishment, of course this is related to international politics which is considered very inhumane. Israel has not ratified the Rome Statute, so the ICC certainly will not be able to process cases of war crimes committed by Israel, making it difficult to hold Israel accountable for violations of the laws of war. In order for the implementation of international humanitarian law enforcement for perpetrators of war crimes, it can be carried out through Internationally Wrongful Acts, it can be realized by carrying out full reparations for losses in the form of restitution, compensation and satisfaction, either separately or in combination.